Electrical and magnetic properties of La0.7Ca0.3MnO3 nanoparticle prepared by reactive milling method. (10th March 2021) - Thi Dung, Nguyen; Van Dang, Nguyen; Thanh, Tran Dang
Abstract: La0.7 Ca0.3 MnO3 nanoparticle in an orthorhombic structure with space group of Pnma was prepared by a combination of the reactive milling method and annealing at 900 °C for 1 h in air. The mean crystal size determined through the powder x-ray diffraction data is 18 ± 2 nm. Based on the dependences of the resistivity and the magnetisation on temperature and applied magnetic field, the electrical-magnetic properties, the magnetoresistance and the magnetocaloric effects have been investigated. It shows La0.7 Ca0.3 MnO3 nanoparticle undergoes a metal-insulator and a ferromagnetic-paramagnetic phase transitions at T MI  = 252 K and T C  = 253 K, respectively. The temperature dependences of resistivity of material in the absence and presence of 4 kOe in a range of 30–300 K were fitted to the phase segregation model. The magnetoresistance and the magnetocaloric effects related to the double-exchange interactions taking place around T MI and T C were observed, corresponding to the values of the magnetoresistance MR = 9.29% and the maximum magnetic entropy change ∣Δ S max ∣ = 0.18 J/kg.K under an applied magnetic field of 4 kOe. Besides, the low field magnetoresistance value at low temperature region and the change of the specific heat of La0.7 Ca0.3 MnO3 nanoparticle have also been concerned.